P455 Comparison of two strategies for the management of post-operative recurrence in Crohn's disease patients with one clinical risk factor: a multicentre IG-IBD study. (30th January 2023) - Dragoni, G; Castiglione, F; Bezzio, C; Pugliese, D; Spagnuolo, R; Viola, A; Cocomazzi, F; Aratari, A; Savarino, E V; Balestrieri, P; Onali, S; Viganò, C; et al.
Abstract: Background: Prevention of postoperative recurrence (POR) in Crohn's disease (CD) after ileo-colonic (IC) resection is still a highly debated topic. Prophylactic immunosuppression after surgery is currently recommended in presence of at least one clinical risk factor (RF). Due to drug-related adverse events and the relative high cost of biologics, we aimed to determine whether prevention of POR can be postponed and guided by endoscopy in CD patients with only one RF. Methods: A multicentre retrospective study was conducted in 12 IG-IBD Italian centres. CD patients with only one RF for POR, including previous intestinal resection, extensive small intestine resection (>50 cm), fistulising phenotype, history of perianal disease, or active smoking were considered. Patients who performed a colonoscopy between 6 to 12 months after curative IC resection were included. Two groups were formed based on whether immunosuppressive therapy was started immediately after surgery (prophylaxis group) or guided by endoscopy (observation group). Primary endpoints were the rates of any endoscopic recurrence (Rutgeerts ≥i2a) and severe endoscopic recurrence (i4) within 12 months after surgery. Secondary outcomes were clinical recurrence (HBI≥5) rates at 6, 12 and 24 months after surgery. Results: A total of 195 patients were enrolled. Out of all, 61 (31.3%) received immunoprophylaxis at a median time of 32 days [IQR 26-55] after surgery (n=14 infliximab, n=37 adalimumab, n=7 azathioprine, n=3 ustekinumab). Baseline patient characteristics are detailed in Table 1. Particularly, risk factors for POR were homogeneously distributed between the 2 groups. Colonoscopy was performed after a median time of 8 months [IQR 6-11]. No differences between immunoprophylaxis and endoscopy-driven approach was found regarding any endoscopic recurrence (36.1% in prophylaxis group vs 45.5% in observation group, p=0.10) and severe endoscopic recurrence (9.8% in prophylaxis group vs 15.7% in observation group, p=0.15). In 32 patients with a second colonoscopy at a median time of 30.5 months [IQR 22-43.75] after surgery, any recurrence and severe recurrence rates were also similar (p=0.55 and p=0.43, respectively). Early clinical recurrence at 6 months was reported in 23.4% of patients on immunoprophylaxis vs 31.5% who were not (p=0.43). Clinical recurrence rates between prophylaxis and observation group were also similar at 12 months (17.9% vs 34.8%, respectively, p=0.09) and at 24 months (17.9% vs 24.1%, respectively, p=0.63). Conclusion: In CD patients with only one RF for POR, immediate immunoprophylaxis after curative IC resection does not decrease the rate of early clinical and endoscopic recurrence. Prospective and larger studies are needed to confirm our results.